Dispute on the Number of Votes in the Election of Head of Tabuyung Village, Muara Batang Girls District, Mandailing Natal Regency from Siyasah Fiqh Perspective (Decision Analysis Study Number: 80/G/2023/Ptun.Medan - Nadilla, Nadilla; Mukhsin, Abd. (LEGAL BRIEF, 2024)
This research aims to understand the dispute resolution mechanism resulting from the election of the Head of Tabuyung Village, Kec. Muara  Batang Gadis, Kab.  Mandailing Natal, focusing on the suitability of legal considerations in the Medan PTUN decision Number: 80/G/2020/PTUN.MEDAN with applicable laws and regulations. And also this writing aims to analyze the basis of the judge's considerations in the Medan PTUN decisions in case Number: 80/G/2020/PTUN.MEDAN.  The Author uses normative research methods with a library approach to collect the necessary legal materials, including sources from experts, perspectives from the perspective of Siyasah Fiqh, research results, and journals related to dispute resolution mechanisms based on statutory regulation